The Function of the Reader in the Formation and the Reception of the Book of Isaiah - van Wieringen, Archibald; Chang, Se-hun (Brill | Schöningh, 2024)
Since the rise of exegesis as a critical science, great emphasis has been placed on the role of the author in the process of the development of the biblical texts. However, with the current literary scientific developments regarding the reader’s position, the exegetical question about the role of the reader should be asked as well. When a text develops, it automatically means that its reader changes. Both the formation and reception of the Isaian text can be understood as a result of this process of changes. What new reader positions were necessary for the development of either new text in the Book of Isaiah, or of new text outside of the Isaiah book, such as the Gospel of Luke? In this edited volume, a group of international Isaiah experts discusses for the first time the various aspects of the role of the reader in the formation and reception of the book of Isaiah.